Around the world in 80 birds - Unwin, Mike (Laurence King Publishing, 2022)
"This beautiful and inspiring book tells the stories of 80 birds around the world: from the Sociable Weaver Bird in Namibia which constructs huge, multi-nest 'apartment blocks' in the desert, to the Bar-headed Goose of China, one of the highest-flying migrants which crosses the Himalayas twice a year. Many birds come steeped in folklore and myth, some are national emblems and a few have inspired scientific revelation or daring conservation projects. Each has a story to tell that sheds a light on our relationship with the natural world and reveals just how deeply birds matter to us." -- Amazon.com.